Illuminating the COP1/SPA Ubiquitin Ligase: Fresh Insights Into Its Structure and Functions During Plant Photomorphogenesis - Ponnu, Jathish; Hoecker, Ute (Frontiers in Plant Science, 2021)
CONSTITUTIVE PHOTOMORPHOGENIC 1 functions as an E3 ubiquitin ligase in plants and animals. Discovered originally in Arabidopsis thaliana, COP1 acts in a complex with SPA proteins as a central repressor of light-mediated responses in plants. By ubiquitinating and promoting the degradation of a number of substrates, COP1/SPA regulates many aspects of plant growth, development and metabolism. In contrast to plants, human COP1 acts as a crucial regulator of tumorigenesis. In this review, we discuss the recent important findings in COP1/SPA research including a brief comparison between COP1 activity in plants and humans.